2013
DOI: 10.1002/jcp.24340
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic use decreases intestinal inflammation and increases bone density in healthy male but not female mice

Abstract: Osteoporosis can result from intestinal inflammation, as is seen with inflammatory bowel disease. Probiotics, microorganisms that provide a health benefit to the host when ingested in adequate amounts, can have anti-inflammatory properties and are currently being examined to treat inflammatory bowel disease. Here, we examined if treating healthy male mice with Lactobacillus reuteri ATCC PTA 6475 (a candidate probiotic with anti-TNFα activity) could affect intestinal TNFα levels and enhance bone density. Adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
211
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(243 citation statements)
references
References 37 publications
19
211
0
Order By: Relevance
“…In addition, this treatment suppressed the ovx-induced increase in bone marrow CD4 + T cells, supporting the notion that the GM modulates the immune status in bone, and thereby affects OCL-mediated bone resorption. In a separate study, oral administration of L. reuteri treatment was shown to decrease intestinal inflammation and increase trabecular bone mass in gonadal intact male mice [53]. Taken together, these studies suggest that treatment with probiotics has beneficial effects on the immune status in bone, which in turn results in attenuated bone resorption in both ovx female mice and intact male mice.…”
Section: Probiotics and Prebioticsmentioning
confidence: 91%
“…In addition, this treatment suppressed the ovx-induced increase in bone marrow CD4 + T cells, supporting the notion that the GM modulates the immune status in bone, and thereby affects OCL-mediated bone resorption. In a separate study, oral administration of L. reuteri treatment was shown to decrease intestinal inflammation and increase trabecular bone mass in gonadal intact male mice [53]. Taken together, these studies suggest that treatment with probiotics has beneficial effects on the immune status in bone, which in turn results in attenuated bone resorption in both ovx female mice and intact male mice.…”
Section: Probiotics and Prebioticsmentioning
confidence: 91%
“…Furthermore, the genes cyclopropane fatty acid synthase (cfa) [43] and L. reuteri-specific immunoregulatory (rsiR) gene [44] have been implicated in the anti-inflammatory properties of L. reuteri 6475. In addition to these immunomodulatory properties in vitro, L. reuteri 6475 has also shown promising effects in animal studies [45][46][47].…”
Section: Immunomodulatory Effects Of Selected Lactic Acid Bacteriamentioning
confidence: 95%
“…Consistent with this, Sjogren et al found that bacterial colonization of young adult GF animals resulted in loss of trabecular bone mass and an increase in bone-resorbing osteoclasts (13). However, other studies have suggested that treatment with beneficial microbes modestly increases bone mineral density (21)(22)(23)(24)(25)(26) and protects against bone loss after sex steroid deficiency (27). Discrepant results in studies examining the effect of microbiota on bone may reflect differences in the composition of the resident microbiota, age of the animal at colonization and necropsy, mouse strain, and sex.…”
mentioning
confidence: 86%